지구중력장모형에 따른 국내 지역별 지오이드고 - 이용창(Yong-Chang Lee) (한국콘텐츠학회 논문지, 8(9), 2008)
The new high order Earth's gravity Model(EGM2008) are expected to improve the application about the Earth's global gravity field. The objectives of this research are to present characteristics on the geoid heights of provinces in South KOREA which calculated from the height anomalies by Earth Gravity Models. For this, seven EGMs (EGM2008<2,190>, EGM2008 , EGM96, EIGEN-GL04C, EIGEN-CG03C, EIGEN-GL04S1, and ITG-Grace02S) selected. Geoid heights of fifty BM check points by GPS/levelling are compared with those by NORI-05 model and seven EGMs. And also, geoid heights of 30"$×$30" grid points in land(sixes blocks ; $1^{°}×1^{°}$ sampled) and sea (four blocks ; $1^{°}×1^{°}$ sampled) areas of South KOREA by EGM2008 are compared with those by NORI-05 and six EGMs. The results show that geoid heights obtained from EGM2008(2,190) of NGA displayed the nearest results to those by GPS/levelling. 최근 새로운 초 고차 지구중력장 모형(EGM2008)의 개발로 인하여 중력관련 응용분야의 향상이 기대되고 있다. 본 연구는 지구중력장모형(EGM)으로부터 남한지역에 대한 고도이상(height anomalies)를 산정하고 지역별 지오이드고의 특성을 분석하였다. 이를 위하여 7가지 지구중력장모형(EGM2008<2,190>, EGM2008 , EGM96, EIGEN-GL04C, EIGEN-CG03C, EIGEN-GL04S1 및 ITG- Grace02S)을 선정하였다. GPS 관측이 수행된 수준점 50개 측점을 점검점으로 선정하여 GPS/Levelling, 국립해양조사원(NORI)의 NORI-05 모형 및 7가지 EGMs에 의한 지오이드 고를 비교 분석하였다. 또한, 남한지역의 경 위도 $1^{°}×1^{°}$ 6개 육상부 및 4개 해상부에 대한 30"$×$30" 격자점을 대상으로 EGM2008 모델에 의한 지오이드고를 NORI-05 모델 및 6가지 EGMs로 부터 구한 결과와 비교하였다. 연구결과, NGA(National Geospatial Intelligence Agency)의 EGM2008(2,190) 모형이 GPS/Levelling 결과에 가장 근접함을 보였다.